Clustering in laboratory and numerical turbulent swirling flows. (10th October 2022) - Angriman, Sofía; Ferran, Amélie; Zapata, Florencia; Cobelli, Pablo J.; Obligado, Martin; Mininni, Pablo D.
Abstract: Abstract : We study the three-dimensional clustering of velocity stagnation points, of nulls of the vorticity and of the Lagrangian acceleration, and of inertial particles in turbulent flows at fixed Reynolds numbers, but under different large-scale flow geometries. To this end, we combine direct numerical simulations of homogeneous and isotropic turbulence and of the Taylor–Green flow, with particle tracking velocimetry in a von Kármán experiment. While flows have different topologies (as nulls cluster differently), particles behave similarly in all cases, indicating that Taylor-scale neutrally buoyant particles cluster as inertial particles.